Factors Of Stimulating The Playing Activity Of Modern Preschoolers - Karapetyan, V. S.; Dallakyan, A. M.; Kobylianska, I. V. (Մանկավարժ հրատ․)
The relevance of the research is due to the necessity to identify the factors stimulating the playing activity of elder preschoolers during the period of fading out of interest in role-playing games. The problem was considered in the context of encouraging non-standard playing actions that do not always contribute to the realization of the main goal of the game; providing an emotional atmosphere in playing; stimulating cognitive dissonance as the main factor in children's cognitive activity in playing. A dependence was revealed between the ability of a preschooler to change the course of the game through non-standard playing actions and the ability to apply purposeful actions in different game situations. A step-by-step method of stimulating the playing activity of preschoolers using the PARLA method is presented. It was found out that stimulating the activity of preschoolers by making purposeful actions in different playing situations contributes to the acquisition of practical skills in the use of conscious actions. Հոդվածում ներկայացված են ավագ նախադպրոցականների խաղային ակտիվության խթանման գործոնները՝ դերային խաղերի նկատմամբ հետաքրքրության նվազման պայմաններում: Մշակված է PARLA մեթոդի փուլայնությամբ իրականացվող, ավագ նախադպրոցականի խաղային ակտիվության խթանման մեթոդիկա, որն ենթադրում է. ա/այլընտրանքային /անսովոր, ոչ միշտ սյուժեից բխող/ խաղային գործողությունների խրախուսում, բ/հուզական փոխազդեցության մթնոլորտի ապահովում, գ/ կոգնիտիվ դիսոնանսի դրսևորումների արձանագրում: В статье представлены факторы, стимулирующие игровую активность старших дошкольников в условиях снижения интереса к ролевым играм. Разработан метод развития игровой деятельности старших дошкольников, поэтапно реализуемый методом ПАРЛА, который предполагает: а) поощрение альтернативных (необычных, не всегда сюжетных) игровых действий, б) обеспечение атмосферы эмоционального взаимодействия, в) фиксация проявлений когнитивного диссонанса.
Keywords: Psychology